High-performance pseudo-halide perovskite nanowire networks for stable and fast-response photodetector. (September 2018) - Asuo, Ivy M.; Gedamu, Dawit; Ka, Ibrahima; Gerlein, Luis Felipe; Fortier, François-Xavier; Pignolet, Alain; Cloutier, Sylvain G.; Nechache, Riad
Abstract: Perovskite-based photodetectors show a great promise thanks to the material's excellent photogeneration and broadband device operation. Amongst the fundamental limitations of halide perovskites, humidity-induced degradation arises as the main impediment towards viable commercial-grade perovskite-based technologies. Here, we report a stable, reproducible and reliable pseudo halide perovskite nanowire network-based photodetector with superior performances. The perovskite nanowire network is deposited using a two-step spin-coating process atop patterned substrates under ambient conditions with relative humidity (RH%), higher than 50%. Because of the particular 1D perovskite nanowire morphology, our devices require no charge collectors, which reduces fabrication steps and costs. Most importantly, we demonstrate that incorporation of lead thiocyanate (Pb(SCN)2 ) directly in the precursor solution promotes the synthesis of stable hybrid perovskite nanowire networks in ambient conditions. These devices exhibit response time as fast as 50 µs and responsivities up-to 0.23 A W −1 at 2 V bias. Also, the optimum photodetector exhibited high specific detectivity of 7.1 × 10 11 cm Hz 1/2 W −1 . This novel and yet simple device architecture brings fabrication challenges to a minimum by allowing synthesis of perovskite nanowires under high humidity conditions. Graphical abstract: fx1 Highlights: A pseudohalide perovskite nanowire network photodetector developed via solution processing in ambient conditions. Synthesis of stable hybrid perovskite nanowire networks via incorporation of thiocyanate (SCN - ) additive. Devices require no charge extractors. 50 µs response time, 0.23 A W −1 responsivities and specific detectivity of 7.1 × 10 11 Jones registered at 490 nm at 2 V bias. Devices show stable, reproducible and high-performance characteristics without additional treatment or constituent required.